Effects of Estradiol Therapy on Resting-State Functional Connectivity of Transgender Women After Gender-Affirming Related Gonadectomy - Schneider, Maiko A.; Spritzer, Poli M.; Minuzzi, Luciano; Frey, Benicio N.; Syan, Sabrina K.; Fighera, Tayane M.; Schwarz, Karine; Costa, Ângelo B.; da Silva, Dhiordan C.; Garcia, Cláudia C. G.; Fontanari, Anna M. V.; Real, André G.; et al. (Frontiers in Neuroscience, 2019)
An extreme incongruence between sex and gender identity leads individuals with gender dysphoria (GD) to seek cross-sex hormone therapy (CSHT) and gender-affirming surgery (GAS). Although a few studies have investigated the effects of CSHT on the brain prior to GAS, there are no studies evaluating its impact during hypogonadism in post-GAS individuals. Here, we aimed to evaluate the effects of estradiol on resting-state functional connectivity (rs-FC) of the sensorimotor cortex (SMC) and basal ganglia following surgical hypogonadism. Eighteen post-GAS (male-to-female) volunteers underwent functional magnetic resonance imaging (fMRI) and neuropsychiatric and hormonal assessment at two time points (t1: hormonal washout and t2: CSHT reintroduction). Based on the literature, the thalamus was selected as a seed, while the SMC and the dorsolateral striatum were targets for seed-based functional connectivity (sbFC). A second sbFC investigation consisted of a whole-brain voxel exploratory analysis again using the thalamus as a seed. A final complementary data-driven approach using multivoxel pattern analysis (MVPA) was conducted to identify a potential seed for further sbFC analyses. An increase in the rs-FC between the left thalamus and the left SCM/putamen followed CSHT. MVPA identified a cluster within the subcallosal cortex (SubCalC) representing the highest variation in peak activation between time points. Setting the SubCalC as a seed, whole-brain analysis showed a decoupling between the SubCalC and the medial frontal cortex during CSHT. These results indicate that CSHT with estradiol post-GAS seems to modulate rs-FC in regions engaged in cognitive, emotional and sensorimotor processes.